Actor-specific contributions to the deforestation slowdown in the Brazilian Amazon - Godar, Javier; Gardner, T; Tizado, J; Pacheco, P. (National Academy of Sciences, 2014)
The Brazilian Amazon is at a critical juncture after the recent stabilization of deforestation rates. Identifying opportunities for continued deforestation reductions requires an understanding of the contribution of different actors to overall deforestation. We provide the first such assessment, to our knowledge, that reports on two headline findings. First, between 2004 and 2011, areas dominated by properties larger than 500 ha accounted for 48% of the deforestation compared with only 12% for smallholders (<100 ha). Second, the deforestation share attributed to the largest properties (≥2,500 ha) declined by 63% from a peak in 2005, whereas that of smallholders increased by 69%. Further reductions in deforestation are likely to require a shift toward more incentive-based policies that are tailored toward different actors.